Systematic review of prosocial behavior measures - Martí-Vilar, Manuel (2018)
Measuring prosocial conduct, just as other constructs which are relevant for psychological adjustment, requires a base of knowledge which is orderly and up-to-date, which helps to identify and methodological aspects for its construction. The objective of this study is to identify the instruments for measuring prosocial behavior which are available today in the empirical literature, as well as to analyze their characteristics and psychometric properties.In this study, the bibliographic search was carried out on the databases of web of science (WOS) and Dialnet from 1900 to 2017 with special emphasis on the last decade. Sixteen instruments relevant to prosocial behavior were chosen describing its applications and characteristics.There is a discussion of the implications of continuing research into measures of prosocial behavior.